ATMPH 2019
DOI: 10.36295/asro.2019.221128
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index of Flakes Made from Mocaf-Black Rice and Bean Flour as Alternative Snacks for People with Type 2 Diabetes Mellitus

Abstract: This study aimed to analyze the glycemic index and glycemic load of mocaf-black rice flakes. The study used a single-factor completely randomized design in which the type of bean flour added were black soybean flour and jack bean flour. The glycemic index was analyzed using the incremental area under the blood glucose response curve (IAUC) method. The glycemic index and glycemic load data were analyzed using paired T-test. The results showed that mocaf-black rice flakes with the addition of black soybean flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Black rice from West Java has anthocyanin content of 126,1% and starch 69,8%. While the amylose content of black rice used has a lower value (16,915%) compared to the amylose content of West Java black rice (26,1%) [22]. Crude fiber in porang flour has a higher value when compared to the research conducted by Nugraheni and Sulistiowati which is 5,025% [23].…”
Section: Raw Materials Characteristicsmentioning
confidence: 79%
“…Black rice from West Java has anthocyanin content of 126,1% and starch 69,8%. While the amylose content of black rice used has a lower value (16,915%) compared to the amylose content of West Java black rice (26,1%) [22]. Crude fiber in porang flour has a higher value when compared to the research conducted by Nugraheni and Sulistiowati which is 5,025% [23].…”
Section: Raw Materials Characteristicsmentioning
confidence: 79%
“…Research finding has shown that low GI-source foods with a low category of GL is correlated with a better glycaemic control (Vlachos et al 2020). In addition, foods with low GI and/or low GL may have a beneficial effect on health, especially in reducing risk factors for diabetes mellitus (Agustia et al 2019). Their finding indicated that all products with additional soybean flour have a low GI value (50.2±21.6).…”
Section: Glycaemic Index and Glycaemic Loadmentioning
confidence: 99%
“…Other product such as soy flour based snack bar could be a potential alternative product for healthy or diabetic people. In a trial study involving normal healthy subjects with normal fasting blood glucose, a normal range of glycaemic response by consumption of snack made from soy flour as additional ingredients after 120 min, has been observed (Agustia et al 2019). A study in Japan indicated that the blood glucose and blood insulin response of diabetic patients after ingestion of a soy nutrition bar made of whole soy flour were significantly lower than test cookie (Urita et al 2012).…”
Section: Introductionmentioning
confidence: 99%